TINGKAT KEPUASAN MAHASISWA TERHADAP KINERJA DOSEN MENGGUNAKAN FUZZY LOGIC (STUDI KASUS DI STTIND PADANG) - Indah Febriyani (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2018)
In higher education, lecturer holding an important role in producing graduates who are qualified and skilled. Therefore, it is necessary to know the student satisfaction measurement on performance of existing on-campus lecturer STTIND Padang. To determine the level of satisfaction of students performed observation and dissemination of the questionnaire to respondents. The questionnaire as a tool for collecting data and the methods used in measuring the level of satisfaction of students against the performance of lecturers is Mamdani Fuzzy Logic method that is implemented through software Matlab 6.1. The results show that students are already quite satisfied on performance lecturer in the course of Mining Engineering at STTIND Padang. By using Fuzzy Logic can generate performance information a lecturer in teaching and can serve as evaluation to improve performance in the future.